Sparking creativity using extrinsic rewards: A self‐determination theory perspective. Issue 6 (9th June 2022) - Lin, Caihui (Veronica); Shipton, Helen; Teng, Weili; Kitt, Adam; Do, Hoa; Chadwick, Clint
Abstract: The relationship between extrinsic rewards and creativity has been subject to ongoing debate within the human resource management and creativity literatures. More research on the mechanisms and boundary conditions has been called for. In this study, using 187 employee‐supervisor dyads in an electronics manufacturing company, we investigated how and when creativity‐contingent extrinsic rewards (CER) may foster creativity among manufacturing employees. Drawing on self‐determination theory, we hypothesized, and found that employee intrinsic motivation mediated the relationship between CER and employee creativity. This relationship was the strongest when employees rated their leader‐member exchange (LMX) as high. The findings reveal the important role of CER in guiding manufacturing employees' intrinsic motivation and stimulating creativity. The identification of LMX as a moderator uncovers crucial boundary conditions of this relationship. Theoretical and practical implications are discussed.